Cardiotoxicity in breast cancer patients: the role of gated myocardial perfusion SPECT. (20th July 2021) - Pacella, S; Bonacina, M; Morzenti, S; Guerra, L; De Ponti, E; Crivellaro, C; Landoni, C; Messa, MC
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients undergoing chemotherapy (CHT) for breast cancer (BC) need a monitoring of cardiac function due to the possible onset of cardiotoxicity. Cardiotoxicity may occur with heart failure but is often asymptomatic and is detectable only by assessing an increase in cardiac volumes (left ventricular end-diastolic (LV-EDV) and end-systolic (LV-ESV) volumes) and/or by a reduction of the left ventricular ejection fraction (LV-EF). The primary purpose of this study was to evaluate the role of gated SPECT myocardial perfusion imaging in this setting. Dosimetric evaluation was also assessed. Methods: Seventeen BC patients (mean age 55.93 ± 11.04 years)with invasive ductal carcinoma HER2 + treated with surgery and with an anthracycline-based adjuvant CHT, were enrolled. The trend of cardiac function was assessed by evaluation of LV-EF, LV-EDV and LV-ESV using gSPECT in baseline conditions and at 12, 15 and 52 weeks during treatment and then at 6, 12, 24 and 48 months during follow-up. Each patient was studied 15-20 min after injection of 555 MBq of 99mTc-Tetrofosmin with gSPECT (16 frames/cardiac cycle) using an Infinia Hawkeye IV gamma-camera. Dosimetry was assed according to ICRP reports. Results: Two out of the 17 patients enrolled left the protocol: one because of a second tumor and the other due to the appearance of cardiotoxicity. 15 patients completed the study: mean LVEF at baseline was 70.67 ± 5.68. The greatest modification occurred after 15th week of treatment, when mean LV-EF showed a significant decrease  to 65.67 ± 8.27, while mean LV-EDV and mean LV-ESV increased from 73.60 ± 16.72 up to 84.73 ± 21.11 and from 21.93 ± 7.17 up to 30.27 ± 14.16, respectively. All parameters progressively returned similar to baseline values at the final examination (after 48th month): mean LV-EF 70.20 ± 5.65, LV-EDV 73.40 ± 16.15 and ESV 22.07 ± 7.50. In one case cardiotoxicity occurred at 15th week: LV-EF decreased from 69 to 47%, LV-EDV increased from 92 up to 142 ml and LV-ESV from 28 up to 75 ml. According to our image protocols, effective dose for gSPECT was 3.83 mSv (ICRP 106). The use of gSPET instead of MUGA (6.47 mSv–ICRP 80) allowed a dose effective saving of 2.64 mSv/each control with a total saving of 21.12 mSv/patient. Conclusions: Although the small sample size, gSPECT was demonstrated to be an applicable tool for monitoring cardiac  function because it correctly identified  BC patient with cardiotoxicity. gSPECT also allowed a significant radiation dose saving compared to MUGA: this is particularly relevant in cardiotoxicity studies that require repeated and close evaluations.